THE PROBLEM OF SCOTS PINE FOREST DECLINE IN THE ZHYTOMYR REGION AND THE PROSPECTS FOR USING THE BIOLOGICAL METHOD OF BARK BEETLE CONTROL - Уваєва, Олена; Пархомчук, Анастасія (SWorldJournal, 2025)
The article addresses the urgent problem of massive Scots pine forest decline in the Zhytomyr region, caused by the active spread of the pine shoot beetle (Ips acuminatus) under conditions of climate change and weakened biostability of forest stands. The